Eksplorasi Bahan Alam (Kerang-Kerang, Pasir, Air Laut) melalui Kegiatan Saintifik pada Anak Usia Dini di Daerah Buton - Siti Misra Susanti; Rachman Saleh; Hartati Hartati; Asma Kurniati; Marwah Marwah; Evi Ervida (Departement of Mathematics Education, 2023)
This study aims to determine the process of exploring natural materials (shellfish, sand, seawater and gravel) through scientific activities in early childhood. The problem is the lack of educators in utilizing natural materials as learning media for early childhood. This activity children observe objects around the beach such as shells, sand and gravel as a vehicle for children's learning. Ask questions related to shells, sand, seawater and gravel, and communicate things that have been observed. This type of research is descriptive qualitative research. the subjects and objects of the study were 8 children, aged 4-5 years in the Buton area. Methods of data collection is done through observation, interviews and documentation. Data analysis techniques were carried out by data reduction, data display and verification. Based on this, it can be concluded that natural product exploration activities are carried out through scientific activities with the steps of observing, asking, gathering information, reasoning/associating and communicating. Children observe natural materials in coastal areas, such as children's activities collecting shells, sand, seawater and gravel, after that children distinguish between many and few, and classify objects based on size. In this activity it was concluded that children are able to carry out exploration activities with natural materials (shells, sea water, gravel and sand) with scientific activities.